Banksy a sprawa palestyńska – przypadek jednego politycznego muralu w Betlejem - Lorenc, Magdalena (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The aim of this paper is to analyze a mural, namely a large wall painting, depicting in this case a white dove with wings spread, carrying an olive branch in its beak and wearing a bulletproof vest, which is in the crosshairs of an unseen weapon. The mural was painted in Bethlehem, Palestine, in 2007 and is attributed to the best known British graffiti artist, who goes by the nickname of Banksy. This white dove mural exemplifies how art can be used for political purposes. This is a gesture of support for the Palestinian issue, namely the Palestinian right to land and, at the same time, it is an expression of criticism of the behavior of Israelis in the territories occupied as a result of the six-day war of 1967. The artist utilized the medium of an urban space painting, with symbols that are easy to understand and interpret in order to convey a political message, while obtaining the following results: the esthetic outcome of making an urban space more attractive; a mobilization effect, by showing methods other than combat for fighting for one’s rights; a promotional one, by making Bethlehem more popular; and commercial, by providing Palestinians with the ‘Banksy’ brand, which is recognized by tourists, to advertise their goods and services.